PENYUSUNAN TEKNOLOGI PEMBELAJARAN BERBASIS PERMAINAN DI SDN BANDENGAN 02 - Hidayah, Nurina; Karimah, Sayyidatul; Susanto, Susanto; Mukti Maliki, Sarah; Maula Ulfa, Halimah (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2024)
Abstract: Game-based learning technology has many advantages and can overcome the low literacy, numeracy skills, and interest in learning of Bandengan 02 elementary school students. However, the resources owned have not been maximally utilized by teachers. So it is necessary to provide assistance in preparing game-based learning technology for teachers. Teachers who are able to develop game-based learning can improve literacy, numeracy, and student interest in learning in the classroom. The method of implementing community service is service learning (SL). Service learning is a learning method that prioritizes service, both to oneself, to others, and to the environment. The assistance provided was in the form of  preparation of a Google Site and Wordwall for learning by teachers of SDN Bandengan 02, numeracy learning assistance in the classroom; and literacy learning assistance in the classroom. The implementation team, consisting of three lecturers and two students, divided the tasks for each of the program plans. The results of the implementation of the activities obtained  an increase in literacy skills by 16% and numeracy by 26% for students of SDN Bandengan 02, and  90% of SDN Bandengan 02 teachers were able to develop a personalized Google Site to facilitate students' independent learning. Keyword: google site; learning technology; literacy; numeracy; service learning  Abstrak: Teknologi pembelajaran berbasis permainan memiliki banyak keunggulan serta mampu mengatasi rendahnya kemampuan literasi, numerasi dan minat belajar siswa SD Bandengan 02. Akan tetapi sumber daya yang dimiliki belum maksimal dimanfaatkan oleh guru. Sehingga perlu adanya pendampingan penyusunan teknologi pembelajaran berbasis permainan untuk guru. Guru yang mampu Menyusun pembelajaran berbasis permainan dapat meningkatkan kemampuan literasi, numerasi serta minat belajar siswa di kelas. Metode pelaksanaan pengabdian kepada Masyarakat yaitu service learning (SL). Service Learning merupakan sebuah metode pembelajaran yang mengutamakan sebuah pelayanan, baik pelayanan terhadap diri sendiri, terhadap orang lain, maupun terhadap lingkungan. Pendampingan yang dilakukan berupa, penyusunan Google Site dan Wordwall untuk pembelajaran oleh guru SDN Bandengan 02, pendampingan pembelajaran numerasi di kelas, pendampingan pembelajaran literasi di kelas. Tim pelaksana yang terdiri dari tiga dosen dan dua mahasiswa membagi tugas untuk masing-masing rencana program tersebut. Hasil pelaksanaan kegiatan diperoleh yaitu  peningkatan kemampuan literasi sebesar 16% dan numerasi sebesar 26% untuk siswa-siswa SDN Bandengan 02, dan  90% Guru-guru SDN Bandengan 02 mampu menyusun Google Site pribadi untuk memfasilitasi siswa belajar secara mandiri. Kata kunci: google site; literasi; numerasi; service learning; teknologi pembelajaran